Heterogeneous policy responses and the risk of monetary disintegration in Europe - Peter K. Cornelius; Thomas Trimbur (Deutsche Bank Research, 2000)
Leaving EMU would create great legal uncertainty and costly litigation and would hence involve extremely high costs for a country that has fully been euronized. Nevertheless, it is conceivable that these costs are not high enough to eliminate fully the risk of monetary disintegration in Europe. In assessing this risk, the paper distinguishes several exit scenarios, whereby particular emphasis is paid to the case where a country decides unilaterally to leave EMU either because of the lack of stabilization efforts in the rest of the union, or, in turn, due to union-wide stabilization efforts which are regarded as excessively ambitious. The empirical results suggest heterogeneous policy responses to macroeconomic strains, implying a non-trivial possibility of escalating tension among the EMU members.
Keywords: E42; 330; EMU; monetary disintegration; Europäische Wirtschafts- und Währungsunion; Separatismus; Inflationsbekämpfung; Finanzpolitik; Nationalstaat; Theorie; EU-Staaten